A comparison of elemental presence in UK and Kuwait road dust. (February 2019) - Alsubaie, Abdullah; Jaafar, Maisarah; Al-Dabbous, Abdullah N.; Alomairy, S.; Altowairqi, Yasir; Daar, Eman; Alkhorayef, Mohammed; Alsulaiti, L.; Almugren, K.S.; Ward, N.I.; Bradley, D.A.
Abstract: The monitoring of concentrations of metals in road dust can be used in evaluating vehicular contributions to the environment. Here we compare the efficacy of several analytical techniques for such samples: XRF, SEM/EDX and ICP-MS, providing for both qualitative and absolute quantitative analysis. To-date we have made evaluation of key elemental levels from roadside dust sampled at different locations within the University of Surrey and the Kuwait Research Institute, in so-doing also investigating the influence of engine size (Kuwaiti vehicles tending to be of larger engine capacity than those in the UK) and the influence of climate, maritime and arid in the present case. With a total of 36 street dust samples collected to-date, 18 have now been analyzed, elemental concentrations being reported for Mg, Al, Ti, Mn, Fe, Co, Zr, Mo, Ba, Tl, V, Rd, Pb, Cu, Zn, Ni, Cr, Cd, As, Hg and Au. For University of Surrey samples, obtained at three different times of the year, SEM/EDX findings range from below the lower limit of detection for Ag, through to 4.7 × 10 −6 mg/m 2 for Co, up to 3.6 × 10 −2 mg/m 2 for Fe. Using ICP-MS on sieved University of Surrey road dust samples similarly taken at different times of the year, mean particle dimensions < 45 µm (i.e. respirable dust) have been obtained yielding elevated elemental concentrations in units of mg/kg (ppm), with mean values as follows: Cu (70.4 mg/kg), Zn (288 mg/kg, ) Al (3081 mg/kg) and Fe (14, 133 mg/kg). These values can be compared against that for Co (3.5 mg/kg) and V (12.3 mg/kg), a primary source of the latter deriving from their use in vehicle tyres production, also for 78.0 mg/kg (Pb). Other toxic metals found in the Guildford and Kuwait samples in different low concentrations were Ti, Cr, and Ba. The concentrations of Pb were found to be low compared to previous analyses, attributable to modern restrictions on Pb in fuel. Au and Ag were also detected, albeit in very low concentrations in the samples from both countries, in particle sizes of the order of 0.5 µm. In summary, present study shows a number of elements presenting at particularly elevated concentrations, a major source being motorpart wear debris. Highlights: A range of predominantly metallic element concentrations in road dust measured. Comparison has been made between concentrations in the UK and Kuwait. With ICP-MS and SEM/EDX, Al, Fe, Mn, and Zn levels were found. Lower Pb levels were found in the UK samples. At smaller particle sizes concentrations are observed to be much enhanced.